Pengaruh pemberian ekstrak rimpang kunyit (Curcuma longa L.) sebagai neuroprotektor terhadap gambaran histopatologi sel otak tikus putih (Rattus norvegicus) jantan galur wistar model alzheimer - Balqis, Ferisha Aulia; Maulina, Meutia; Novalia, Vera (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Alzheimer’s disease is a neurodegenerative disorder that leads to cognitive decline and memory loss, eventually impairing daily activities. Turmeric (Curcuma longa L.) has neuroprotective potential due to its curcumin content, which possesses anti-inflammatory, antioxidant, and neuroprotective properties. This study aims to examine the effect of different doses of turmeric rhizome extract on the histopathological features of brain cells in Wistar rats (Rattus norvegicus) induced with Alzheimer’s disease. An experimental study with a post-test only control group design was conducted using simple random sampling. A total of 24 male Wistar rats were divided into four groups: K1 (Alzheimer-induced without treatment), K2 (administered 20 mg/kgBW memantine), P1 (Alzheimer-induced with 36 mg/kgBW turmeric extract), and P2 (Alzheimer-induced with 54 mg/kgBW turmeric extract). The results showed the highest percentage of cell necrosis in K1 (19.7%), while the lowest was in K2 (1.67%), followed by P2 (2.5%) and P1 (5%). The Kruskal-Wallis test indicated a significant difference between groups p = 0.030 (p < 0.05). The Post Hoc Mann-Whitney test revealed a significant difference between K1 and both K2 and P2. These findings suggest that turmeric rhizome extract at a dose of 54 mg/kgBW has a neuroprotective effect by reducing neuronal necrosis in Alzheimer-induced rats. However, no significant difference was observed between the memantine-treated group and the turmeric extract-treated groups. There was no significant difference between the group given memantine treatment and the group given turmeric rhizome extract (Curcuma Longa L.).